Exploration of Critical Thinking Skills in Digital Citizenship Course Through Online Learning - Herwati, Titan Istiah; Basori, Basori; Hatta, Puspanda (IJIE (Indonesian Journal of Informatics Education), 2020)
Low critical thinking skills cause students difficulty in solving problem, especially in learning. This study aims to find out the effectiveness of google classroom on critical thinking skills in Simulation dan Digital Communication. A total of 62 students participated in this research who were divided into two randomized treatments, namely 31 students in the experimental class and 31 students in the control class. In its implementation, it would compare using LMS google classroom by applying discussion groups to experimental class and control class that use google classroom, not in discussion groups. This research used a quasi experimental design with a pretest-posttest using a quantitative method. The data were collected through a critical thinking test. Before using multiple-choice pretest and posttest multiple-choice tests, instruments were tested first using validity tests and reliability tests. Google classroom as an independent variable and the dependent variable was critical thinking. Implementing learning with the help of google classroom through discussion and question features was an effort to effectively improve critical thinking skills in class. According to the result of the study, google classroom has effectiveness on critical thinking skills from the result in the experimental class of 45.609 Increased critical thinking skills in students cause students to analyze and solve problems.